Pertanggungjawaban Hukum Notaris Pengganti dalam Pembuatan Akta Melampaui Kewenangan di Indonesia - Simangunsong, Gaby Handayani; Simamora, Janpatar (Politica: Jurnal Hukum Tata Negara dan Politik Islam, 2024)
A substitute notary is a temporary official appointed to perform the duties of a primary notary during their absence, such as during leave or illness. Under Law No. 2 of 2014 concerning the Notary Office, a substitute notary holds the authority to create authentic deeds and manage protocols, similar to a primary notary. However, exceeding this authority poses significant legal risks, potentially invalidating deeds and leading to serious legal consequences. This study examines the legal responsibilities of substitute notaries in ensuring the validity of deeds they produce, emphasizing the importance of adhering to their defined authority and professional ethical standards. It aims to analyze the implications of substitute notaries exceeding their authority in drafting deeds, particularly in terms of deed validity and legal accountability. Furthermore, the research highlights the necessity of limiting substitute notary authority and implementing strict supervision to uphold the integrity of notarial practices. Using a normative legal method (juridical-normative), the study analyzes laws and regulations through a literature review and qualitative analysis of primary, secondary, and tertiary legal sources. The findings reveal that the legal liability of substitute notaries for deeds made beyond their authority encompasses civil, criminal, and administrative aspects. Such actions can render deeds invalid and cause harm to the parties involved. This research contributes to the field by providing a comprehensive understanding of the legal and ethical boundaries that substitute notaries must respect, offering insights for policymakers to enhance regulatory frameworks and supervision mechanisms. It also serves as a reference for legal practitioners and scholars to identify preventive measures and solutions to mitigate the risks associated with notarial misconduct.